The Phenomenon of Interpersonal Communication of Unikom Students on the Bumble Application in Searching for Partners - Firdaus, Moch Raihan; Oxcygentry, Oky; Muslimah, Tikka (Universitas Tanjungpura, 2025)
This study analyzes the interpersonal communication patterns of Bumble app users in finding a partner and identifies the inhibiting factors, based on the Social Penetration Theory by Altman and Taylor. Using a descriptive qualitative method and in-depth interviews with five Unikom Bandung students who use Bumble, this study examines how gradual self-disclosure forms online intimacy. The results show that communication patterns are in line with the stages of Social Penetration Theory: starting from Orientation (formal communication, shallow self-disclosure, influenced by the